Analysing the impact of massclusivity campaigns on luxury and mass-market fashion brands - Santos, J. F.; Bilro, R.G.; Loureiro, S. M. C. (2019 Global Fashion Management Conference at Paris Proceedings, 2019)
The current research aims to explore the impact of Massclusivity campaigns (massive and exclusive) (Brogi et al., 2009; Silverstein and Fiske, 2003) on the brand love of online brand communities. In this sense, this study comprises (i) the analysis of the meaning and perception of luxury, (ii) the marketplace associated to luxury – with a focus on the fashion consumption segment, (iii) and the impact of trends such as digital luxury and Massclusivity. We intend to explore the dynamics of the selected market based on the core of relationship marketing concepts, brand love, brand communities and consumerbrand relationship.